Home Monitoring Programs for Patients Testing Positive for SARS-CoV-2: An Integrative Literature Review - Lara, Brenda; Kottler, Janey; Olsen, Abigail; Best, Andrew; Conkright, Jessica; Larimer, Karen (Applied Clinical Informatics, 2022)
Background The severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) pandemic threatened to oversaturate hospitals worldwide, necessitating rapid patient discharge to preserve capacity for the most severe cases. This need, as well as the high risk of SARS-CoV-2 transmission, led many hospitals to implement remote patient monitoring (RPM) programs for SARS-CoV-2 positive patients in an effort to provide care that was safe and preserve scarce resources.Objective The aim of this study is to provide an integrative review of peer-reviewed literature on different RPM programs that were implemented for SARS-CoV-2 positive patients including their strengths and challenges.Methods A search was conducted for peer reviewed literature using PubMed, CINAHL, OVID, and Google Scholar. Peer-reviewed studies written in English or Spanish and published between 2019 and 2021 on RPM of SARS-CoV-2-positive patients were considered. Information was extracted according to a qualitative content analysis method, informed by the Comparison of Mobile Patient Monitoring Systems Framework.Results Of 57 retrieved articles, 10 publications were included. The sample sizes ranged from 75 to 48,290 and the monitoring length ranged from 7 to 30 days. Information regarding the comparison framework was summarized. Main strengths of using RPM for SARS-CoV-2 positive patients was participant acceptance, feasibility, safety, and resource conservation. Main limitations were the lack of information on patient data security measures, robust outcomes testing, and identification of the most effective biomarkers to track SARS-CoV-2 decompensation.Conclusion Different RPM programs for SARS-CoV-2 were implemented, from sending home participants with a pulse oximeter and collecting readings via call to modifying existing mobile applications and sending holistic health questionnaires to participants. This review determined that RPM is beneficial to SARS-CoV-2 positive patients; however, its effectiveness can be improved by further research. Mainly, identifying what patient data are most effective at tracking SARS-CoV-2 decompensation by utilizing advanced technology already in the market.
Keywords: SARS-CoV-2; COVID-19; coronavirus; remote patient monitoring; telehealth; home quarantine; infectious disease; emergency medicine